Penggunaan Media Play Dough untuk Meningkatkan Kreativitas Anak Kelompok B di TK GMIM Joseph Kam Kamenti Kapataran Satu Kecamatan Lembean Timur - Paputungan, Hasnawati (Peneliti.net, 2024)
The background for carrying out the research was because the creativity of group B children at the GMIM Josep Kam Kamenti Kapataran Satu Kindergarten was still low. The aim of this research was to increase children's creativity through the use of playdough media. The research method used is Classroom Action Research model Kemmis and Mc. Taggart is carried out twice in cycles with the steps namely planning, implementation, observation and reflection. The subjects of this research were 11 GMIM Josep Kam Kamenti Kapataran One Kindergarten children. The data collection techniques used were observation and field notes as well as data analysis using assessment techniques in kindergarten. The results of the research showed that cycle I was 54.5% and cycle II experienced an increase after improvements were made to 100%, thus the increase that occurred from cycle I to cycle II was 45.5%. It was concluded that the use of playdough media in learning activities can increase children's creativity at the GMIM Joseph Kam Kamenti Kindergarten. It is recommended that kindergarten teachers use playdough media to increase children's creativity